A core-shell structure precursor and its preparation method and application

By adopting the front -drive system preparation method of the shell nuclear structure in the positive electrode material of the sodium ion battery, the core layer of the O3 phase and the shell of a variety of transition metal elements solves the problem of unstable the existing positive electrode material structure. Capacity and cycle performance.

CN118724086BActive Publication Date: 2025-01-28PAWA (ZHUJI) NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411227841.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-28
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The layered metal oxides of the positive electrode materials of existing sodium ion batteries are unstable in the deep desodium state and are prone to phase change, resulting in a decline in the overall performance of the battery.

Method used

The front -drive system preparation method of the shell nuclear structure is used to prepare the nuclear through the sedimentation method, and then form a hydroxide shell layer with a variety of transition metal elements on the nucleus. element.

Benefits of technology

It improves the initial capacity and electrochemical activity of the positive pole material, delayed and highly reversible O3 to P3 phase transformation process, maintaining the stable material structure, and improving the battery ratio and cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118724086B_ABST
    Figure CN118724086B_ABST
Patent Text Reader

Abstract

The invention belongs to the field of sodium ion battery materials and discloses a method for preparing a precursor with a shell-core structure. The method comprises the following steps: firstly preparing a core containing nickel, iron and manganese, and then in-situ precipitating five metal elements of Ni, Mn, Fe, Cu and Zn or any five or more metal elements of Ni, Cu, Mg, Fe, Co, Mn, Ti, Sn and Sb on the core to obtain a precursor with a shell-core structure; then mixing the precursor with sodium and sintering the precursor to obtain an O3 phase positive electrode material core, which can make the positive electrode material have a larger initial capacity; the positive electrode material contains a plurality of transition metal elements in its shell, which makes the positive electrode material have a higher electrochemical activity, and the O3 to P3 phase change process in the positive electrode material is significantly delayed and highly reversible during the charging and discharging process, which can keep the material structure stable, thereby improving the specific capacity and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sodium ion battery materials and relates to a body material, in particular to a core-shell structure precursor and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have become an ideal candidate for large-scale energy storage due to their abundant resources, low cost, and high safety. Among the currently known sodium-ion battery positive electrode materials, sodium layered metal oxides have attracted widespread attention due to their high theoretical specific capacity and easy synthesis.

[0003] The layered structure of layered metal oxides is unstable under deep sodium removal and is prone to phase transition, which leads to the destruction of the layered metal oxide structure. Phase transition under high voltage can easily cause a large change in the unit cell volume, affecting the Na + Diffusion. The formation of microcracks on the surface of positive electrode particles and the aggregation of solid electrolyte intermediate phases can also easily lead to electrode failure. The above situations will lead to a decrease in the overall performance of the battery. Therefore, there is an urgent need to provide a stable and high-capacity sodium ion layered oxide positive electrode material. Summary of the invention

[0004] In view of the above problems existing in the prior art, in the first aspect, the present invention provides a method for preparing a core-shell structure precursor; in the second aspect, the present invention provides a core-shell structure precursor; in the third aspect, the present invention provides a positive electrode material; finally, the present invention provides a battery.

[0005] In a first aspect, the present invention provides a method for preparing a core-shell structure precursor, comprising the following steps:

[0006] Step 1, nucleation stage, nickel-iron-manganese mixed salt solution, sodium hydroxide solution and ammonia water are introduced into the reaction system and reacted for a certain time under a protective atmosphere;

[0007] Step 2, shell formation stage, continuously introduce M metal mixed salt solution, sodium hydroxide and ammonia water into the reaction system, react for a certain time under protective atmosphere to obtain slurry A, and then filter and dry the slurry A to obtain the precursor;

[0008] M in the M salt is Ni, Mn, Fe, Cu, and Zn, or any five or more of Ni, Cu, Mg, Fe, Co, Mn, Ti, Sn, and Sb, and the molar ratios of any five or more of the elements are the same.

[0009] Preferably, in step 2, the shell forming stage includes a first stage and a second stage; in the first stage, a nickel-iron-manganese mixed salt solution, an M metal mixed salt solution, a sodium hydroxide solution and an ammonia solution are introduced under a protective atmosphere, and the flow rate of the nickel-iron-manganese mixed salt solution gradually decreases until it reaches 0 and then enters the second stage, and the M metal mixed salt solution, sodium hydroxide solution and an ammonia solution are continuously introduced into the reaction system, and the reaction is carried out for a certain period of time under a protective atmosphere.

[0010] Preferably, in step 1, the flow rate of the nickel-iron-manganese mixed salt solution in the early stage of the reaction is 1-4 L / h lower than the flow rate of the nickel-iron-manganese mixed salt solution in the late stage of the reaction; wherein, the reaction enters the late stage when the D50 of the precipitated particles is 3 μm.

[0011] Further preferably, in step 1, in the early stage of the reaction, the flow rate of the nickel-iron-manganese mixed salt solution is 2-7 L / h; in the late stage of the reaction, the flow rate of the nickel-iron-manganese mixed salt solution is 6-8 L / h.

[0012] Preferably, in step 2, the flow rate of the M metal salt solution is 1-3 L / h.

[0013] Preferably, in the nickel-iron-manganese mixed salt solution and the M metal mixed salt solution, the nickel salt, iron salt, manganese salt and M salt are soluble salts; further preferably, the soluble salt is one or more of sulfate, acetate, halogen salt and nitrate.

[0014] Preferably, the molar ratio of nickel ions, manganese ions and iron ions in the nickel-iron-manganese mixed salt solution is 0.2-0.4:0.2-0.5:0.2-0.4, and the values ​​of nickel ions, manganese ions and iron ions in the nickel-iron-manganese mixed salt solution satisfy the charge balance of the chemical formula; further preferably, the total concentration of nickel ions, manganese ions and iron ions in the nickel-iron-manganese mixed salt solution is 1-3 mol / L.

[0015] Preferably, the total concentration of metal ions in the M metal mixed salt solution is 1-3 mol / L.

[0016] Preferably, in step 1 and step 2, the pH value of the reaction system is 10-12; the reaction temperature is 40-70°C; more preferably, the reaction temperature is 55-65°C.

[0017] Preferably, in step 1, the ammonia concentration of the reaction system is 2-10 g / L; in step 2, the ammonia concentration of the reaction system is 2-6 g / L.

[0018] Further preferably, in step 2, the ammonia concentration of the reaction system is 2-4 g / L.

[0019] Further preferably, as the D50 of the precipitated particles increases, the pH values ​​in step 1 and step 2 gradually decrease, and the pH value in step 2 is lower than the pH value in step 1.

[0020] Further preferably, in step 1, as the D50 of the precipitated particles increases, the pH value of the reaction system is reduced by 0.05-0.15 every 8-16 hours; in step 2, as the D50 of the precipitated particles increases, the pH value of the reaction system is reduced by 0.05-0.15 every 6-14 hours.

[0021] Preferably, in step 1 and step 2, the concentration of the sodium hydroxide solution is 2-10 mol / L; the mass concentration of the ammonia solution is 4-12%.

[0022] Preferably, in step 1 and step 2, the oxygen content in the gas atmosphere of the reaction system is less than 5%.

[0023] Preferably, an aging stage is further included after step 1 and step 2.

[0024] In a second aspect, the present invention provides a core-shell structure precursor prepared by the above preparation method.

[0025] Preferably, the precursor comprises a core and a shell, wherein the shell covers at least a portion of the surface of the core; the general formula of the core is: Ni a Mn b Fe c (OH)2, 0.2≤a≤0.4, 0.2≤b≤0.5, 0.2≤c≤0.4, a+b+c=1; the shell layer includes M element, M is Ni, Mn, Fe, Cu, Zn or any five or more of Ni, Cu, Mg, Fe, Co, Mn, Ti, Sn, Sb, and the molar ratio of any five or more elements is the same.

[0026] Preferably, the thickness of the shell layer is preferably 0.2-0.8 μm.

[0027] Preferably, the precursor is spherical or quasi-spherical.

[0028] In a third aspect, the present invention provides a positive electrode material, which is obtained by sintering a precursor obtained by the above preparation method or by mixing the above precursor material with a sodium source.

[0029] Preferably, in the sintering stage, the mixture of the precursor material and the sodium source is pre-sintered at 400-500° C. for 4-6 hours, and then the temperature is raised to 900-1000° C. and sintered for 12-18 hours.

[0030] Finally, the present invention provides a battery comprising the positive electrode material.

[0031] Compared with the prior art, the present invention has the following obvious beneficial technical effects:

[0032] (1) The precursor provided by the present invention is mixed with sodium and sintered, and the core of the obtained positive electrode material is in the O3 phase, which can make the positive electrode material have a large initial capacity; the shell of the positive electrode material contains a variety of transition metal elements, which makes the positive electrode material have a high electrochemical activity. During the charge and discharge process, the O3 to P3 phase transition process in the positive electrode material is significantly delayed and highly reversible, which can maintain the structural stability of the material, thereby improving the specific capacity and cycle performance of the battery.

[0033] (2) The preparation method provided by the present invention is simple, controllable, low-cost, and easy to implement, which is conducive to promotion and marketization. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a SEM image of the precursor material prepared in Example 1 of the present invention.

[0035] Figure 2 This is a SEM image of the cross section of the precursor material prepared in Example 1 of the present invention.

[0036] Figure 3 XRD test diagram of the positive electrode material obtained by mixed sodium sintering of the precursors of Example 1 (NNMFMZ) of the present invention and Comparative Example 1 (NNMF).

[0037] Figure 4 This is a test chart of the cycle performance of the positive electrode material obtained by sintering the precursors prepared in Example 1-3 and Comparative Example 1-2 at a 2C rate. DETAILED DESCRIPTION

[0038] The present invention provides the following specific technical solutions.

[0039] In a first aspect, the present invention provides a method for preparing a core-shell structure precursor, comprising the following steps:

[0040] Step 1, nucleation stage, nickel-iron-manganese mixed salt solution, sodium hydroxide solution and ammonia water are introduced into the reaction system and reacted for a certain time under a protective atmosphere;

[0041] Step 2, shell formation stage, continuously introduce M metal mixed salt solution, sodium hydroxide and ammonia water into the reaction system, react for a certain time under protective atmosphere to obtain slurry A, and then filter and dry the slurry A to obtain the precursor;

[0042] M in the M salt is Ni, Mn, Fe, Cu, and Zn, or any five or more of Ni, Cu, Mg, Fe, Co, Mn, Ti, Sn, and Sb, and the molar ratios of any five or more of the elements are the same.

[0043] The inventors have found through research that a precursor is prepared by a precipitation method, a core is prepared first, and then in-situ precipitation is performed on the core to form a hydroxide shell containing five or more metal elements. The positive electrode material is prepared using the precursor, and the inner core of the prepared positive electrode material is in an O3 phase, which can make the positive electrode material have a larger initial capacity; the shell of the positive electrode material contains a variety of transition metal elements, which makes it have a higher electrochemical activity, and the positive electrode material has a higher electrochemical activity. During the charge and discharge process, the O3 to P3 phase change process in the positive electrode material is significantly delayed and highly reversible, which can keep the structure of the material stable, thereby improving the specific capacity and cycle performance of the battery.

[0044] Preferably, in step 2, the shell forming stage includes a first stage and a second stage; in the first stage, a nickel-iron-manganese mixed salt solution, an M metal mixed salt solution, a sodium hydroxide solution and an ammonia solution are introduced under a protective atmosphere, and the flow rate of the nickel-iron-manganese mixed salt solution gradually decreases until it reaches 0 and then enters the second stage, and the M metal mixed salt solution, sodium hydroxide solution and an ammonia solution are continuously introduced into the reaction system, and the reaction is carried out for a certain period of time under a protective atmosphere.

[0045] When preparing the shell layer, a nickel-iron-manganese mixed salt solution is introduced, which can play a guiding role on the one hand, guiding the transition metal ions of various components to precipitate to the core surface; on the other hand, it can play a transition role, forming a transition layer between the core and the shell.

[0046] Preferably, in step 1, the flow rate of the nickel-iron-manganese mixed salt solution in the early stage of the reaction is lower than the flow rate of the nickel-iron-manganese mixed salt solution in the late stage of the reaction; wherein, the reaction enters the late stage when the D50 of the precipitated particles is 3 μm.

[0047] Further preferably, in step 1, in the early stage of the reaction, the flow rate of the nickel-iron-manganese mixed salt solution is 2-7 L / h; in the late stage of the reaction, the flow rate of the nickel-iron-manganese mixed salt solution is 6-8 L / h.

[0048] The inventors have found through research that in the early stage of nucleation, controlling the flow rate of the nickel-iron-manganese mixed salt solution at a low level is conducive to nucleation and prevents particle agglomeration. In the late stage of nucleation, increasing the flow rate of the nickel-iron-manganese mixed salt solution can accelerate particle growth, shorten time costs, and increase output.

[0049] Preferably, in step 2, the flow rate of the M metal salt solution is 1-3 L / h.

[0050] Studies have shown that controlling the flow rate of the M metal salt solution at a lower level can allow the shell to be evenly coated on the core, thereby improving the coating effect.

[0051] Preferably, in step 2, after the M metal mixed salt solution is introduced, the flow rate of the nickel-iron-manganese mixed salt solution gradually decreases until it reaches 0.

[0052] The precursor is prepared by the precipitation method, and the concentration gradient of the doping element in the precursor can be adjusted by adjusting the flow rate. The operation is simple and controllable.

[0053] Preferably, in the nickel-iron-manganese mixed salt solution and the M metal mixed salt solution, the nickel salt, iron salt, manganese salt and M salt are soluble salts. More preferably, the soluble salt is one or more of sulfate, acetate, halogen salt and nitrate.

[0054] Preferably, the molar ratio of nickel ions, manganese ions and iron ions in the nickel-iron-manganese mixed salt solution is 0.2-0.4:0.2-0.5:0.2-0.4, and the values ​​of nickel ions, manganese ions and iron ions in the nickel-iron-manganese mixed salt solution satisfy the charge balance of the chemical formula; further preferably, the total concentration of nickel ions, manganese ions and iron ions in the nickel-iron-manganese mixed salt solution is 1-3 mol / L.

[0055] Preferably, the total concentration of metal ions in the M metal mixed salt solution is 1-3 mol / L.

[0056] Preferably, in step 1 and step 2, the pH value of the reaction system is 10-12; the reaction temperature is 40-70°C; more preferably, the reaction temperature is 55-65°C.

[0057] Preferably, in step 1, the ammonia concentration of the reaction system is 2-10 g / L; in step 2, the ammonia concentration of the reaction system is 2-6 g / L.

[0058] Further preferably, in step 2, the ammonia concentration of the reaction system is 2-4 g / L.

[0059] Further preferably, in step 1, as the precipitated particles D50 increase, the pH value of the reaction system is reduced by 0.05-0.15 every 8-16 hours; in step 2, as the precipitated particles D50 increase, the pH value of the reaction system is reduced by 0.05-0.15 every 6-14 hours.

[0060] The inventor has found through research that in step 1, the pH value is high in the early stage of the reaction, which is conducive to the rapid precipitation of the nucleus. As the reaction proceeds, the pH value is gradually reduced, which is conducive to the growth of the nucleus and avoids the occurrence of particle agglomeration and uneven particle size. In step 2, the pH value is gradually reduced as the reaction proceeds, so that the shell layer gradually thickens and the entire particle grows. In the actual production process, the pH value is adjusted by adjusting the flow rate of sodium hydroxide. In step 1, the flow rate of the sodium hydroxide solution is gradually reduced as the nucleus grows; after entering step 2, the flow rate of the sodium hydroxide solution is reduced again.

[0061] Preferably, in step 1 and step 2, the concentration of the sodium hydroxide solution is 2-10 mol / L.

[0062] Preferably, in step 1 and step 2, the concentration of aqueous ammonia is 4-12%.

[0063] In actual production, the concentration of sodium hydroxide solution and the concentration of ammonia water can be adjusted according to actual conditions. The concentration of sodium hydroxide solution and the flow rate of sodium hydroxide solution determine the pH value in the reaction system, and the flow rate of sodium hydroxide solution is adjusted according to the pH value at different stages in the reaction system. The concentration of ammonia water and the flow rate of ammonia water determine the ammonia concentration in the reaction system, and the flow rate of ammonia water is adjusted according to the ammonia concentration at different stages in the preset reaction system.

[0064] Preferably, the oxygen content in the gas atmosphere of the reaction system is less than 5%.

[0065] The oxygen content in the reaction system will affect the growth process of the precursor and ultimately affect the physical and chemical properties of the precursor. A high oxygen content will accelerate the growth of the precursor, making the surface of the precursor rough, increasing the specific surface area, and low tap density. It is also easy to cause small nuclei to form on the surface of the precursor, affecting the electrochemical properties of the positive electrode material.

[0066] Preferably, an aging stage is further included after step 1 and step 2.

[0067] In a second aspect, the present invention provides a core-shell structure precursor prepared by the above preparation method.

[0068] Preferably, the precursor comprises a core and a shell, wherein the shell covers at least a portion of the surface of the core; the general formula of the core is: Ni a Mn b Fe c (OH)2, 0.2≤a≤0.4, 0.2≤b≤0.5, 0.2≤c≤0.4, a+b+c=1; the shell layer includes M element, M is Ni, Mn, Fe, Cu, Zn or any five or more of Ni, Cu, Mg, Fe, Co, Mn, Ti, Sn, Sb, and the molar ratio of any five or more elements is the same.

[0069] Preferably, the thickness of the shell layer is preferably 0.2-0.8 μm.

[0070] In actual situations, the coating thickness of the shell layer can be adjusted according to actual conditions. The coating thickness depends on the length of the coating time. The thickness of the shell layer is preferably 0.2-0.8 μm. Too thick a shell layer affects the capacity, and too thin a shell layer affects the cycle performance.

[0071] Preferably, the precursor is spherical or quasi-spherical.

[0072] In a third aspect, the present invention provides a positive electrode material. The present invention provides a positive electrode material obtained by sintering a precursor obtained by the above preparation method or by mixing the above precursor material with a sodium source.

[0073] The inventors have found through research that the core of the precursor mixed with sodium sintered by the preparation method provided by the present invention is in the O3 phase, which can make the positive electrode material have a large initial capacity, and the high entropy oxide shell made of at least five metal elements has a significant delay in the phase transition from O3 to P3 during the charge and discharge process and is highly reversible, which improves the structural stability of the material. And after the shell coats the core, the contact area between the core and the electrolyte can be reduced, thereby reducing the occurrence of interface side reactions and improving the cycle stability.

[0074] M is composed of at least five metal elements. Multiple groups of elements can maximize the mixing entropy of the material, inhibit the formation of intermetallic compounds, and promote the formation of solid solution single phase. The atomic-level combination between the active components and the inactive components (MgO) inside the material can effectively prevent the agglomeration of transition metal oxide nanoparticles. At the same time, the atomic hysteresis diffusion effect inside the material slows down the aggregation of secondary particles, which is beneficial to maintaining the structural stability of the active material and the integrity of the electrode.

[0075] Preferably, the ratio of the precursor material and the sodium source is prepared according to a commonly used ratio; the sodium source is also a commonly used sodium source, preferably sodium nitrate.

[0076] Preferably, in the sintering stage, the mixture of the precursor material and the sodium source is pre-sintered at 400-500° C. for 4-6 hours, and then the temperature is raised to 900-1000° C. and sintered for 12-18 hours.

[0077] Finally, the present invention provides a battery comprising the positive electrode material.

[0078] In order to make the technical problems to be solved, technical solutions and technical advantages of the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0079] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0080] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0081] Embodiment 1:

[0082] A method for preparing a core-shell structure precursor comprises the following steps:

[0083] Step 1, add 30L of clean water, 2.4L of 8% ammonia water and 90ml of 32% sodium hydroxide solution to a 50L reactor and stir for 2h, while introducing nitrogen to replace the gas in the reactor. Prepare a nickel-iron-manganese mixed salt solution, wherein the molar ratio of Ni:Mn:Fe is 0.3:0.4:0.3, and the concentration of metal elements in the nickel-iron-manganese mixed salt solution is 2mol / L. Prepare an M metal mixed salt solution, wherein the M elements are Ni, Mn, Fe, Cu and Zn, the molar ratio of Ni:Mn:Fe:Cu:Zn is 1:1:1:1:1, and the concentration of metal elements in the M metal mixed salt solution is 2mol / L.

[0084] Step 2, continuously pass nickel-iron-manganese mixed salt solution, 5mol / L sodium hydroxide solution, and 8% ammonia water into the bottom liquid of the reactor, control the oxygen content in the reaction system to be less than 5%, adjust the initial pH value of the reaction system to 11.60, the ammonia concentration to 6g / L, the rotation speed to 700rpm, the initial flow rate of nickel-iron-manganese mixed salt solution to 3L / h, the initial flow rate of sodium hydroxide solution to 1.2L / h, and the initial flow rate of ammonia solution to 0.3L / h, and reduce the flow rate of sodium hydroxide every 12h to make the pH value of the reaction system drop by 0.1, and the flow rate of ammonia solution to maintain an ammonia concentration of 6g / L for adjustment. When the D50 of the precipitated particles is ≥3.0μm, the flow rate of the nickel-iron-manganese mixed salt solution is raised to 7L / h, and when the D50 of the precipitated particles is 5.5±0.3μm, stop passing the nickel-iron-manganese mixed salt solution, sodium hydroxide solution and ammonia water, and statically age for 2h to obtain Ni 0.3 Mn 0.4 Fe 0.3 (OH)2 nuclear material.

[0085] Step 3, into the reaction system, nickel iron manganese mixed salt solution, M metal mixed salt solution, 5mol / L sodium hydroxide solution, 8% ammonia water, adjust the initial pH value of the reaction system to 11.00, ammonia concentration of 3g / L, the rotation speed of 700rpm, the initial flow rate of nickel iron manganese mixed salt solution is 7L / h, the flow rate of sodium hydroxide solution is 2.5L / h, the flow rate of ammonia solution is 0.3L / h, and the flow rate of M metal mixed salt solution is 2L / h. After the reaction starts, the flow rate of the nickel iron manganese mixed salt solution continues to decrease, and the flow rate is reduced to 0L / h within 12h. Every 10h, the pH is reduced by 0.1 by reducing the flow rate of sodium hydroxide. When the D50 of the precipitated particles is 6.0 ± 0.3μm (the total reaction time is about 40h), stop passing the M metal mixed salt solution, sodium hydroxide solution and ammonia water, and after static aging for 2h, wash with alkali, wash with water, and dry to obtain a precursor.

[0086] Figure 1 is a SEM schematic diagram of the precursor prepared in Example 1 of the present invention, Figure 1It can be seen that the precursor prepared by the present invention is spherical, uniformly coated, and has no agglomeration phenomenon.

[0087] Figure 2 is a SEM image of a cross section of the precursor obtained in Example 1 of the present invention. Figure 2 It can be seen that the precursor core prepared by the present invention is relatively dense, and the shell is relatively loose.

[0088] Comparative Example 1:

[0089] A method for preparing a precursor comprises the following steps:

[0090] Step 1: Add 30L of clean water, 2.4L of 8% ammonia water and 90ml of 32% sodium hydroxide solution into a 50L reactor and stir for 2h, while introducing nitrogen to replace the gas in the reactor. Prepare a nickel-iron-manganese mixed salt solution, wherein the molar ratio of Ni:Mn:Fe is 0.3:0.4:0.3, and the concentration of metal elements in the nickel-iron-manganese mixed salt solution is 2mol / L.

[0091] Step 2, continuously pass nickel-iron-manganese mixed salt solution, 5mol / L sodium hydroxide solution, and 8% ammonia water into the bottom liquid of the reactor, control the oxygen content in the reaction system to be less than 5%, adjust the initial pH value of the reaction system to 11.60, the ammonia concentration to 6g / L, the rotation speed to 700rpm, the initial flow rate of nickel-iron-manganese mixed salt solution to 3L / h, the initial flow rate of sodium hydroxide solution to 1.2L / h, and the initial flow rate of ammonia solution to 0.3L / h, and reduce the flow rate of sodium hydroxide every 12h to make the pH drop by 0.1, and the flow rate of ammonia solution to maintain an ammonia concentration of 6g / L is adjusted. When the D50 of the precipitated particles is ≥3.0μm, the flow rate of the nickel-iron-manganese mixed salt solution is raised to 7L / h. When the D50 of the precipitated particles is 6.0±0.3μm, stop passing nickel-iron-manganese mixed salt solution, sodium hydroxide solution and ammonia water, and statically age for 2h to obtain Ni 0.3 Mn 0.4 Fe 0.3 (OH)2 precursor.

[0092] Comparative Example 2:

[0093] A method for preparing a core-shell structure precursor comprises the following steps:

[0094] Step 1: Add 30L of clean water, 2.4L of 8% ammonia water and 90ml of 32% sodium hydroxide solution into a 50L reactor and stir for 2h, while introducing nitrogen to replace the gas in the reactor. Prepare M metal mixed salt solution, wherein M elements are Ni, Mn, Fe, Cu and Zn, the molar ratio of Ni:Mn:Fe:Cu:Zn is 1:1:1:1:1, and the concentration of metal elements in the M metal mixed salt solution is 2mol / L.

[0095] Step 2: introduce M metal mixed salt solution, 5 mol / L sodium hydroxide solution, and 8% ammonia water into the reaction system, adjust the initial pH value of the reaction system to 11.00, the ammonia concentration to 3 g / L, the rotation speed to 700 rpm, the flow rate of the sodium hydroxide solution to 2.5 L / h, the flow rate of the ammonia solution to 0.3 L / h, and the flow rate of the M metal mixed salt solution to 2 L / h. Every 10 hours, the pH is reduced by 0.1 by reducing the flow rate of sodium hydroxide. When the D50 of the precipitated particles is 6.0±0.3 μm (the total reaction time is about 40 hours), stop introducing the M metal mixed salt solution, sodium hydroxide solution, and ammonia water, and after static aging for 2 hours, wash with alkali, wash with water, and dry to obtain the precursor.

[0096] Embodiment 2:

[0097] Step 1, add 30L of clean water, 2.4L of 8% ammonia water and 90ml of 32% sodium hydroxide solution to a 50L reactor and stir for 2h, while introducing nitrogen to replace the gas in the reactor. Prepare a nickel-iron-manganese mixed salt solution, wherein the molar ratio of Ni:Fe:Mn is 0.4:0.3:0.3, and the concentration of metal elements in the nickel-iron-manganese mixed salt solution is 1mol / L. Prepare an M metal mixed salt solution, wherein the M elements are Ni, Co, Ti, Cu and Sn, the molar ratio of Ni:Co:Ti:Cu:Sn is 1:1:1:1:1, and the concentration of metal elements in the M metal mixed salt solution is 1mol / L.

[0098] Step 2, continuously pass nickel-iron-manganese mixed salt solution, 2mol / L sodium hydroxide solution, and 4% ammonia water into the bottom liquid of the reactor, control the oxygen content in the reaction system to be less than 5%, adjust the initial pH value of the reaction system to 11.40, the ammonia concentration to 2g / L, the rotation speed to 700rpm, the initial flow rate of nickel-iron-manganese mixed salt solution to 2L / h, the initial flow rate of sodium hydroxide solution to 1.2L / h, and the initial flow rate of ammonia solution to 0.3L / h, and reduce the flow rate of sodium hydroxide every 8h to make the pH drop by 0.05, and the flow rate of ammonia solution to maintain an ammonia concentration of 6g / L for adjustment. When the D50 of the precipitated particles is ≥3.0μm, the flow rate of the nickel-iron-manganese mixed salt solution is raised to 6L / h. When the D50 of the precipitated particles is 5.8±0.3μm, stop passing nickel-iron-manganese mixed salt solution, sodium hydroxide solution and ammonia water, and statically age for 2h to obtain Ni 0.4 Mn 0.3 Fe 0.3 (OH)2 nuclear material.

[0099] Step 3, into the reaction system, nickel iron manganese mixed salt solution, M metal mixed salt solution, 2mol / L sodium hydroxide solution, 4% ammonia water, the initial pH value of the reaction system is 10.80, the ammonia concentration is 2g / L, the rotation speed is 700rpm, the initial flow rate of nickel iron manganese mixed salt solution is 7L / h, the flow rate of sodium hydroxide solution is 2.5L / h, the flow rate of ammonia solution is 0.3L / h, and the flow rate of M metal mixed salt solution is 1L / h. After the reaction starts, the flow rate of nickel iron manganese mixed salt solution continues to decrease, and the flow rate is reduced to 0L / h within 12h. Every 6h, the pH is reduced by 0.05 by reducing the flow rate of sodium hydroxide. When the D50 of the precipitated particles is 6.0 ± 0.3μm, the M metal mixed salt solution, sodium hydroxide solution and ammonia water are stopped, and after static aging for 2h, the precursor can be obtained by alkali washing, water washing and drying.

[0100] Embodiment 3:

[0101] Step 1, add 30L of clean water, 2.4L of 8% ammonia water and 90ml of 32% sodium hydroxide solution to a 50L reactor and stir for 2h, while introducing nitrogen to replace the gas in the reactor. Prepare a nickel-iron-manganese mixed salt solution, wherein the molar ratio of Ni:Mn:Fe is 0.3:0.4:0.3, and the concentration of metal elements in the nickel-iron-manganese mixed salt solution is 3mol / L. Prepare an M metal mixed salt solution, wherein the M elements are Ni, Mn, Fe, Mg and Ti, the molar ratio of Ni:Mn:Fe:Mg:Ti is 1:1:1:1:1, and the concentration of metal elements in the M metal mixed salt solution is 3mol / L.

[0102] Step 2, continuously pass nickel-iron-manganese mixed salt solution, 10mol / L sodium hydroxide solution, and 12% ammonia water into the bottom liquid of the reactor, control the oxygen content in the reaction system to be less than 5%, adjust the initial pH value of the reaction system to 11.90, the ammonia concentration to 6g / L, the rotation speed to 700rpm, the initial flow rate of nickel-iron-manganese mixed salt solution to 7L / h, the initial flow rate of sodium hydroxide solution to 1.2L / h, and the initial flow rate of ammonia solution to 0.3L / h, and reduce the flow rate of sodium hydroxide every 16h to make the pH drop by 0.15, and the flow rate of ammonia solution to maintain an ammonia concentration of 6g / L for adjustment. When the D50 of the precipitated particles is ≥3.0μm, the flow rate of the nickel-iron-manganese mixed salt solution is raised to 8L / h. When the D50 of the precipitated particles is 5.0±0.3μm, stop passing nickel-iron-manganese mixed salt solution, sodium hydroxide solution and ammonia water, and statically age for 2h to obtain Ni 0.3 Mn 0.4 Fe 0.3 (OH)2 nuclear material.

[0103] Step 3, into the reaction system, nickel iron manganese mixed salt solution, M metal mixed salt solution, 10mol / L sodium hydroxide solution, 12% ammonia water, the initial pH value of the reaction system is adjusted to 11.20, the ammonia concentration is 4g / L, the rotation speed is 700rpm, the initial flow rate of nickel iron manganese mixed salt solution is 7L / h, the flow rate of sodium hydroxide solution is 2.5L / h, the flow rate of ammonia solution is 0.3L / h, and the flow rate of M metal mixed salt solution is 2L / h. After the reaction starts, the flow rate of nickel iron manganese mixed salt solution continues to decrease, and the flow rate is reduced to 0L / h within 12h. Every 14h, the pH is reduced by 0.15 by reducing the flow rate of sodium hydroxide. When the D50 of the precipitated particles is 6.0 ± 0.3μm, the M metal mixed salt solution, sodium hydroxide solution and ammonia water are stopped, and the precursor can be obtained by alkali washing, water washing and drying after static aging for 2h.

[0104] The precursors prepared in Examples 1-3 and Comparative Examples 1-2 were respectively mixed with sodium nitrate at a mass ratio of 1:1.105 and then pre-calcined at 450°C for 5 hours in an oxygen atmosphere in a tube furnace, and finally calcined at 950°C for 15 hours. After cooling, the positive electrode material was obtained.

[0105] Figure 3 It is the XRD test pattern of the positive electrode material obtained after mixed sodium sintering of the precursors prepared in Example 1 (NNMFMZ) of the present invention and Comparative Example 1 (NNMF). The positive electrode material prepared in Comparative Example 1 is in O3 phase, and the peak of the positive electrode material prepared in Example 1 is basically consistent with the peak of the positive electrode material prepared in Comparative Example 1, which can confirm that the core of the positive electrode material provided by the present invention is O3 phase.

[0106] The positive electrode materials prepared by the precursors prepared in Examples 1-3 and Comparative Examples 1-2 were mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent. The mixture was placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a slurry. The slurry was coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for 4h, punched into a pole piece with a diameter of 14mm, and then dried at 105°C in a vacuum drying oven for 4h, placed in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.1ppm for 4h to reduce the moisture adsorbed during the pole piece transfer process, and then assembled into a CR2032 button battery in the glove box. The battery uses a pure metal sodium sheet with a diameter of 16 mm and a thickness of 0.5 mm as the negative electrode, and a porous polyethylene film of model Celgard2300 with a diameter of 18 mm as the separator. After the battery is assembled and aged for 12 hours, the charge and discharge tests at different potentials are carried out. At a voltage of 4.5 V, it is activated at 0.1C for 3 cycles and then cycled at a rate of 2C for 100 cycles. The test data of the battery assembled from the positive electrode material obtained from the precursor prepared in Examples 1-3 and Comparative Examples 1-2 are shown in Table 1 below.

[0107] Table 1 Test data of batteries assembled from positive electrode materials obtained from precursors obtained in Examples 1-3 and Comparative Examples 1-2

[0108]

[0109] Figure 4 This is a test chart of the cycle performance of a battery assembled with positive electrode materials prepared by sintering the precursors prepared in Example 1-3 and Comparative Example 1-2 with sodium mixture at a 2C rate.

[0110] The thickness of the shell layer in Example 2 is 0.2 μm, and the thickness of the shell layer in Example 3 is 1 μm. By comparing the capacity retention rates of Example 2 and Example 3, it can be seen that the thickness of the shell layer affects the initial capacity and cycle performance. A shell layer that is too thick affects the capacity, and a shell layer that is too thin affects the cycle performance.

[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a core-shell structure precursor, characterized in that: The steps include: Step 1, nucleation stage, nickel-iron-manganese mixed salt solution, sodium hydroxide solution and ammonia water are introduced into the reaction system and reacted for a certain time under a protective atmosphere; Step 2, shell formation stage, continuously introduce M metal mixed salt solution, sodium hydroxide and ammonia water into the reaction system, react for a certain time under protective atmosphere to obtain slurry A, and then filter and dry the slurry A to obtain the precursor; M in the M salt is Ni, Mn, Fe, Cu, Zn or any five or more of Ni, Cu, Mg, Fe, Co, Mn, Ti, Sn, Sb, and the molar ratio of any five or more elements is the same; In step 2, the shell formation stage includes a first stage and a second stage; in the first stage, a nickel-iron-manganese mixed salt solution, an M metal mixed salt solution, a sodium hydroxide solution and an ammonia solution are introduced under a protective atmosphere, and the flow rate of the nickel-iron-manganese mixed salt solution gradually decreases until it reaches 0 and then enters the second stage, and the M metal mixed salt solution, sodium hydroxide solution and an ammonia solution are continuously introduced into the reaction system, and the reaction is carried out for a certain time under a protective atmosphere.

2. The method for preparing a core-shell structure precursor according to claim 1, characterized in that: In the nickel-iron-manganese mixed salt solution and the M metal mixed salt solution, the nickel salt, iron salt, manganese salt and M salt are soluble salts; the soluble salts are one or more of sulfates, acetates, halogen salts and nitrates; the molar ratio of nickel ions, manganese ions and iron ions in the nickel-iron-manganese mixed salt solution is 0.2-0.4:0.2-0.5:0.2-0.4, and the values ​​of nickel, iron and manganese in the nickel-iron-manganese mixed salt solution satisfy the charge balance of the chemical formula.

3. The method for preparing a core-shell structure precursor according to claim 1, characterized in that: In step 1, the flow rate of the nickel-iron-manganese mixed salt solution in the early stage of the reaction is 1-4 L / h lower than the flow rate of the nickel-iron-manganese mixed salt solution in the late stage of the reaction; wherein, the reaction enters the late stage when the D50 of the precipitated particles is 3 μm.

4. The method for preparing a core-shell structure precursor according to claim 1, characterized in that: In step 1 and step 2, the pH value of the reaction system is 10-12; the reaction temperature is 40-70° C.; in step 1, the ammonia concentration of the reaction system is 2-10 g / L; in step 2, the ammonia concentration of the reaction system is 2-6 g / L.

5. The method for preparing a core-shell structure precursor according to claim 1 or 4, characterized in that: As the D50 of the precipitated particles increases, the pH values ​​in step 1 and step 2 gradually decrease, and the pH value in step 2 is lower than the pH value in step 1.

6. A core-shell structure precursor, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.

7. The core-shell structure precursor according to claim 6, characterized in that: The precursor comprises a core and a shell, wherein the shell at least covers a portion of the surface of the core; the general formula of the core is: Ni a Mn b Fe c (OH)2, 0.2≤a≤0.4, 0.2≤b≤0.5, 0.2≤c≤0.4, a+b+c=1; the shell layer includes M element, M is Ni, Mn, Fe, Cu, Zn or any five or more of Ni, Cu, Mg, Fe, Co, Mn, Ti, Sn, Sb, and the molar ratio of any five or more elements is the same; the thickness of the shell layer is 0.2-0.8μm.

8. A positive electrode material, characterized in that The precursor prepared by the preparation method according to any one of claims 1 to 5 or the precursor according to any one of claims 6 to 7 is mixed with a sodium source and then sintered; in the sintering stage, the mixture of the precursor material and the sodium source is first pre-sintered at 400-500°C for 4-6h, and then the temperature is raised to 900-1000°C and sintered for 12-18h.

9. A battery, characterized in that: Comprising the positive electrode material as claimed in claim 8.

Citation Information

Patent Citations

  • Modified high energy density lithium ion battery anode material and preparation method thereof

    CN103779554A

  • Core-shell structure sodium ion battery positive electrode material and preparation method and application thereof

    CN110277540A